Research in progress - evaluation of smart card acceptance : security, technology and usage - Taherdoost, Hamed; Masrom, Maslin; Ismail, Zuraini (2009)
Today smart cards are used all over the world as personal identification cards for corporate building security systems and personal computer equipment access control. Governments, financial services, telecommunications, healthcare, education, retail, and many other industries are using smart cards as a means of providing better security and improved services to its customers and users. In this context, user acceptance is a key for successful implementation of the smart card program. The purpose of this study is to present an overview of smart cards, and evaluate user’s acceptance in terms of security, technology and usage of smart cards. A pilot study was carried out, and a total of 50 questionnaires were distributed to graduate students in the field of computer science (major in Information Security and Software Engineering) of the University Technology Malaysia. The questions asked included five areas comprised of characteristics of smart card, usage, technology, security and acceptance. The open-ended questions are also included to examine users’ opinion regarding the current use of smart card.